Engineered stromal vascular fraction for tissue regeneration - Liu, Jianfeng; Li, Yiwei; Zhang, Yanan; Zhao, Zhiwei; Liu, Bin (Frontiers in Pharmacology, 2025)
The treatment of various tissue injuries presents significant challenges, particularly in the reconstruction of large and severe tissue defects, with conventional clinical methods often yielding suboptimal results. However, advances in engineering materials have introduced new possibilities for tissue repair. Bioactive components are commonly integrated with synthetic materials to enhance tissue reconstruction. Stromal vascular fraction (SVF), an adipose-derived cell cluster, has shown considerable potential in tissue regeneration due to its simple and efficient way of obtaining and its richness in growth factors. Therefore, this review illustrated the preparation, characterization, mechanism of action, and applications of engineered SVF in various tissue repair processes, to provide some references for the option of better methods for tissue defect reconstruction.